2019
DOI: 10.1002/star.201800336
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Responsive Starch‐Citrate Nanoparticles for Controlled Release of Paracetamol

Abstract: Starch‐citrate samples with degrees of substitution (DS) ranging from 0.11 to 0.90 are synthesized by a green esterification reaction between citric acid and native sago starch (Metroxylon sagu) in an aqueous medium. Starch‐citrate nanoparticles with mean diameter of 105 nm are subsequently obtained by controlled precipitation through drop‐wise addition of dissolved starch‐citrate solution into excess absolute ethanol. These nanoparticles are observed to exhibit pH‐responsive release profiles within the physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Cell assays confirmed that DBS‐NPs exhibited nontoxicity and high biocompatibility. Chin, Romainor, Pang, Lee, and Hwang (2019) prepared citrate‐modified starch with degrees of substitution (DS) ranging from 0.11 to 0.90 and then fabricated nanoparticles with a mean diameter of 105 nm. Cytotoxicity studies of the HaCaT cell line (human skin cells) showed that the nanoparticles were nontoxic and suitable for biomedical applications as pH‐responsive drug carriers.…”
Section: Digestibility and Toxicity Of Starch‐based Nanoparticlesmentioning
confidence: 99%
“…Cell assays confirmed that DBS‐NPs exhibited nontoxicity and high biocompatibility. Chin, Romainor, Pang, Lee, and Hwang (2019) prepared citrate‐modified starch with degrees of substitution (DS) ranging from 0.11 to 0.90 and then fabricated nanoparticles with a mean diameter of 105 nm. Cytotoxicity studies of the HaCaT cell line (human skin cells) showed that the nanoparticles were nontoxic and suitable for biomedical applications as pH‐responsive drug carriers.…”
Section: Digestibility and Toxicity Of Starch‐based Nanoparticlesmentioning
confidence: 99%
“…The results showed that these nanoparticles were effective in encapsulating two chemically distinct drugs (indomethacin and ibuprofen sodium) with varying hydrophobicities. They also found that the controlled Ahmad et al (2012) Pea starch Quercetin Evaluation of release kinetics Farrag et al (2018) Sago palm starch Curcumin Bioavailability of curcumin Chin, Mohd, et al (2014) Sago palm starch -pH-responsive drug carriers Tay, Pang, and Chin (2012) Sago palm starch Paracetamol pH-responsive drug carriers Chin, Romainor, Pang, Lee, and Hwang (2019) Sago palm starch Curcumin Bioavailability of curcumin Pang et al (2015) Banana starch Curcumin Oral drug delivery Acevedo-Guevara et al 2018Jackfruit seed starch Ibuprofen Colon-targeted drug delivery Das and Das (2019) Jack bean starch -Nanoparticle disintegrants in drug delivery systems Oladebeye (2020) Cassava (Manihot esculentus) starch Rifampicin Tuberculosis treatment Christianah and Rodrigues (2016) Cassava (variety H-165) Curcumin Cancer therapy Athira and Jyothi (2015) TA B L E 4 (Continued) F I G U R E 2 Comparison between two drug-loading methods used for ciprofloxacin loading on starch nanoparticles (StNPs). (a) Flow chart of the coating method.…”
Section: S Tarch -Ba S Ed Nanoparticle S For Drug Delivery Applic Amentioning
confidence: 99%
“…The weight of the swollen starch nanoparticles was determined at various time intervals. 13 The swelling ratio was determined based on Equation 2:…”
Section: Swelling Studiesmentioning
confidence: 99%